Disrupting information alters the behavioral response to a mutual signal trait in both sexes of Nicrophorus (Coleoptera: Silphidae) burying beetles. (3rd April 2019) - Wormington, Jillian D; Luttbeg, Barney
Abstract: Effective signals transfer information in a way that enhances the fitness of the sender. Signal traits are often sexually dimorphic. However, in some species, males and females display similar signals, and these mutual signals are less often studied. Competition for resources occurs in both males and females, and mate choice is likely to occur whenever mates vary in quality and reproductive investment is high. Nicrophorus burying beetles compete intrasexually over the carrion resources on which they biparentally raise their young. Nicrophorus species also often have clypeal membranes which scale hyperallometrically with body size, exaggerating the apparent body size of larger individuals. To examine the potential signaling function of clypeal membranes, we examined the behavioral responses of male and female Nicrophorus orbicollis and Nicrophorus pustulatus burying beetles to same- and opposite-sex social partners which had their membranes painted black or clear. We found evidence that blocking the information in clypeal membranes affected intrasexual aggressive interactions for both sexes of both species. Blocking a female's signal reduced the likelihood of mating attempts for male N. pustulatus, whereas blocking a male's signal influenced female rejection behaviors in N. orbicollis . Our results show that males and females can experience similar selection pressures, and suggest that examining mutual signals in a broader range of systems will expand our understanding of evolutionary differences and similarities between the sexes. Abstract : We found a rare example of a colorful signal displayed by males and females used in same-sex competition over a resource other than mates. Burying beetles compete within their sexes for resources and pairs parent cooperatively. They have orange/red membranes above their jaws that they use to communicate. We found that covering the membrane changed same-sex interactions for both sexes in 2 species, indicating that shared signals can arise through nonsexual competition.